FAKTOR APA SAJAKAH YANG MEMPENGARUHI PEMAHAMAN STANDAR AKUNTANSI KEUANGAN PADA IMPLEMENTASI KURIKULUM MERDEKA? - Lucia Ari Diyani; Chita Oktapriana; Huda Aulia Rahman (Faculty of Economics and Business, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) Program has been launched since 2020. One of the requirements is that the courses offered are courses without prerequisites, but in practice there are courses with prerequisites. MBKM participants come from different study programs, so they have different absorption capacities. On the basis of these problems, a research idea emerged to look for factors that influence understanding of Financial Accounting Standards in the implementation of MBKM. The population uses MBKM participants in odd semester 2021/2022 Intermediate Accounting classes who come from public and private universities in Indonesia. Sampling using a purposive non-random method, more precisely judgment sampling. 124 respondents met the requirements and after conducting moderated regression analysis, the results of simultaneous testing were Education, Study Period, and Accounting Insights which had a positive effect on the understanding of all financial accounting standards issued by the Ikatan Akuntan Indonesia. While testing separately, Accounting Education and Insights had a positive effect but Study Period had no effect. In addition, the variable majors in high school are not able to moderate the influence of Education, Study Period and Accounting Insights on understanding of financial accounting standards. Research results can contribute input to universities and the government.